Geological conditions for the development of geothermal energy in Azerbaijan - A.V. Islamzade; A.Sh. Mukhtarov (Геофизический журнал, 2024)
The article considered the thermal waters existing in Azerbaijan, the prospects for their use, business opportunities and other issues. Forecast operational reserves of thermal waters in the Republic, renewable energy potential of Azerbaijan, including the share of renewable energy in Azerbaijan in 2020 are reflected here. Thus, there are a large number of closed and unused exploration wells that can be restored and used to generate geothermal energy with less investment. Now the main goal is to determine the optimal location for drilling wells with a higher geothermal potential and the problems of using this energy. Thermal waters with different chemical composition and mineralization in Azerbaijan are predominantly common in the fold regions of the Caucasus and Talysh Mountains and have significant reserves. As a result of research conducted on more than 1,000 thermal water sources in Azerbaijan, it was determined that the total reserve of thermal water is more than 245´103 m3/day. The main discharge paths of these waters are tectonic faults of different directions and amplitudes. The gas content of the thermal water sources of the Greater Caucasus and Talysh mountains are methane, nitrogen, hydrogen-sulfur mixture, and the content of the Lesser Caucasus’ are mainly carbon dioxide. Methane waters are usually high-pressure and high-flow, and high-temperature (64—95 °C). The number of sources containing methane is up to 200. Such sources include Masalli (Arkivan), Devechi (Ledzh), Salyan (Babazanan) and others. Sources of nitrogen are found in the southern part of the Greater Caucasus and in Talysh. These include both cold (14—180 °С) and hot (41—550 °С) springs. The highest nitrogen content among them is Alasha — 100 % (Astara), Meshesu 100 % (Lankaran), Ledzh — 37 %, Khaltan — 88 % (Devechi).